Results of Minimally Invasive Plate Osteosyntheses in Periarticular Knee Fractures (Journal of Pakistan Orthopaedic Association, 2017)
Objectives: To evaluate the outcome of periarticular knee fractures treated with MIPO technique.Methods: This descriptive cross sectional study was conducted from January 2012 to December 2014. Data including: age, gender, mechanism of injury, bone involved, Final outcome and complications during surgery were recorded on a pre-formed proforma. Knee Society score was used to assess the final   outcome.Results: There were 26 patients, 16 (61.5%) male and 10 (38.5%) female. The overall mean age was 37.15 years±3.64 (SD) (17-65years).  11(42.3%) patients had distal femur fracture while 15 (57.7%) patients had proximal tibial fracture. 22 (84.6%) patients had closed fractures while open fractures in 4 (15.4%) patients, all involving proximal tibia. Mean union time for distal femur was 15.55week2.98 (SD) (10-20weeks), while mean time for union of proximal tibia was 18.33weeks+_3.56 (SD) (12-24 weeks). Mean follow-up was 11.88months 7.1(SD)(8-20months). According to Knee Society Score, Clinical results were excellent in 6 (23.1%) patients, good in 16(61.5%) patients, fair in 2(7.7%) patients, and poor in 2(7.7%) patients. Functional outcome was excellent in 6(23.1%) patients, good in 17(65.4%) patients and poor in 3 (11.5%) patients.Conclusion: MIPO is well-documented technique and achieves good biological fixation in periarticular knee fractures with good results and low complication rates.